Семантичні паралелі в символіці бобових, злакових та заліза в уявленнях давніх слов'ян і сучасних східнослов'янських народів - Тупчієнко, М. (Народна творчість та етнологія, 2019)
Стаття базується на залученні етнографічних, лінгвістичних та археологічних джерел. Автор переконливо показує, що символіка матеріалів дозволяє розкрити спрямованість екологічної культури минулих етнічних спільнот. Розглядається цілісність та послідовність світогляду народу на різних етапах історичного розвитку. На основі наведеного матеріалу автор говорить про генетичний зв'язок двох міфологічних кодів творення світу деміургом у давніх слов'ян – кулінарного та металургійного. Незважаючи на те, що кулінарний давніший за металургійний і безпосередньо вплинув на формування останнього. The article is based on the attraction of ethnographic, linguistic, and archaeological sources. The author shows convincingly that the symbolism of materials allows revealing the orientation of the ecological culture of the past ethnic communities. The integrity and consistency of the people’s worldview at various stages of historical development are considered. The conducted research has shown that the parallels of semantic combinations of peas, cereals and iron in the Ukrainians traditional culture have a multifaceted character, namely: 1) peas and grain crops are identified with iron through identification with the stars; 2) with the universe structure as a world tree represented by beans and cereals; 3) through the comparison of the technology of grain and iron treatment (threshing and rubbing); 4) in the influence of the culinary code of the main myth on the formation of its version – the metallurgical code (in the terms of the metal boiling, the ball dough, lending of bread shape to the bloom); 5) an ability to generate sounds similar to thunder (flatulence, musical instruments filled with peas, iron forging, weapons peal, etc.); 6) in the fairy-tale images of the iron grandfather and iron grandmother living in the peas, iron bread and iron beans, the image of Kotyhoroshko, born from a pea, armed with an iron mace, finally with the expression in the times of the Pea king, used to denote the period of mythological cosmogenesis; 7) Christmas rite to stimulate the fertility of fruit trees – beating them with a sack of peas or an axe. Various scenarios of the cosmogonic act of reproduction are realized in this ritual. On the one hand, it is the world creation together with the fruit trees from the iron (broader metal) pea—a star falling from the sky. And on the other hand, it is a script of the main myth about the struggle of the Thunderer with his adversary, where an axe is a weapon of the god Hromovyk. Therefore, based on the given material, one can speak confidently about the genetic connection of two mythological codes of the world creation by the demiurge of ancient Slavs—culinary and metallurgical ones. Although culinary is older than metallurgical, and has directly influenced the formation of the latter.